Electronically controllable first-order multifuntion filter with using single active building block - Chinpark, Kobkiat; Jaikla, Winai; Siripongdee, Surapong; Suwanjan, Peerawut (My University, 2018)
In this paper, a new voltage-mode first-order multifunction filter using the modified current controlled current conveyor transconductance amplifier (M-CCCCTA) is presented. The proposed filter has two input-voltage nodes with single output voltage node. It can realize three first-order filtering output responses, low-pas filter (LPF), high-pass filter (HPF) and all-pass filter (APF). The natural frequency is electronically tuned. For all-pass filter, the phase shift is electronically varied from 0 to 180 degree which is conveniently controlled by microprocessor or microcontroller. Also, the matching condition of the parameter used to tune the phase response is not required. The proposed first-order filter employs single grounded capacitor, single grounded resistor, and single M-CCCCTA. The simulation results from PSpice program are included to confirm workability of the proposed filter.
Keywords: all-pass filter; CCCCTA; electronic controllability; first-order circuit; high-pass filter; low-pass filter; voltage-mode circuit